3y-x-3=0

Simple and best practice solution for 3y-x-3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-x-3=0 equation:


Simplifying
3y + -1x + -3 = 0
Reorder the terms:
-3 + -1x + 3y = 0
Solving
-3 + -1x + 3y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3' to each side of the equation.
-3 + -1x + 3 + 3y = 0 + 3
Reorder the terms:
-3 + 3 + -1x + 3y = 0 + 3
Combine like terms: -3 + 3 = 0
0 + -1x + 3y = 0 + 3
-1x + 3y = 0 + 3
Combine like terms: 0 + 3 = 3
-1x + 3y = 3
Add '-3y' to each side of the equation.
-1x + 3y + -3y = 3 + -3y
Combine like terms: 3y + -3y = 0
-1x + 0 = 3 + -3y
-1x = 3 + -3y
Divide each side by '-1'.
x = -3 + 3y
Simplifying
x = -3 + 3y

You can always share this solution

See similar equations:

| y=4x^2+32x+61 | | -4r+2=-5r+10 | | 2(y-3)=2y-9+y | | -7a-3=9+6a | | 0.4x+9.6=7.8 | | -9p+2=-7p-5-3p | | 7+2(5k+4)=-21-2k | | 5n+2=-14-n | | 18x^3=21x^2+72x | | 32m=64 | | 0.6x-1.5=8.1 | | -2m=9-5m | | 2x^4-12x^3+4x^2-38x+84=0 | | -3m=9-5m | | 42x^2-12x= | | a=b-1x-2+cx-1 | | .20(12+x)=.6+.35x | | 8x+5+3x+9+4x+4=180 | | 5z-10z=7z | | .3(12+x)=.6+.35x | | 6+p+7p=3p+6+5p | | s+2+2s-10=180 | | 10=30x+10 | | -6-5j+1=-3j+9 | | 12x-6=3(x+9) | | 13(x-2)=8x-6 | | 690= | | 10=-30x+10 | | (w)=0 | | .25(12+x)=.6+.35x | | 9p^2-12p=0 | | (w)=1 | | (w)=-1 | | -9n^2-9=315 | | 5+6x+25=180 | | (w)=-2 | | 8-10p=88 | | 4c-10=-9+3c | | (7y+2)(y-5)= | | 8x(8+6x)=20 | | .25(12x)=.6+.35x | | -2(x-4)=-6(2+x) | | 5(x+1)+51=-2x | | 4x+14=6x-26 | | 2m+7(m-1)=-21-5m | | 5+6y=5y+10 | | -abx^2+bcx+1=0 | | 5+y^2+7=3 | | 15w-22=-111 | | 8v+4=2v-8 | | 4(x-4)+2x=4x-6 | | (6y+5)(y-2)= | | 13x+7=6x+14 | | -3+7q=-7+9q | | -(1+6m)+6m=-11+3(r-7) | | Y=(5t^2)*(5t^3) | | -2(3)(-5)= | | 3(7-4x)=-39 | | 12=96 | | 3x+3+55=180 | | 4(5x-7)=52 | | 4x^3-34x^2+70x-25=0 | | -5s-9=-2s | | 2x^2-12x=32x-192 | | 3(-7+7x)=168 |


Related pages


2x-4y 4simplifying calculator with steps252-100what is the square root of 1369fx 3xsolving multi step equations calculator480 344 6200square root of 7225sen 2xroman numerals for 1990whatisab17x2f x g x1973 roman numeralsis 4xy 2y 9 a linear equationsimplify x 2y 3prime factorization of 83calculator equation solverderivative of 1 cosxgraph of y 2x 3graph 5x 250v5001.8fprime factorization of 630subtracting fractions calculator show workgcf of 84lcm of 2 and 51abcwhat is 0.625 as a percentage210-500.41666 as a fractionsimplify 2xfind the prime factorization of 8prime factorization 994ab2 3ab2256-192vf 2 vi 2 2ad999 in roman numerals847.1algebra calculator step by stepprime factorization of 169solve 2sin 2x 14x2 4x 112abclog6 1how to solve 2x 5y 10math solutions solversolve the equation x2 5x 0what is the lcm of 4ax2 bx c 0 solvesimplify square root 96what is the prime factorization for 120factor x 2 11x 24prime factorization of 266find the prime factorization of 99simplify 2x 5write 88 as a product of prime factorswhat is sin 2x equal to1975 roman numeralsdifferentiation calculatorwhat is 6 of 2086 roman numeralsxcosx757-100derivative of ln 4xfx tanx4j websitehow to divide fractions on calculatorwhat is 1.5 percent as a decimalfactor 5x-15solve 3x-2y 24n36roman numeral for 74differentiate 2e x12.5 percent as a decimal